Contributions to our knowledge of the biology of Machiloides Delanyi Wygodzinsky and Ctenolepisma Longicaudata Escherich : (Hexapoda Thysanura) - Heeg, J. (Jan) (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1963)
Among the South African Thysanura, the order Lepismatoidea has spread over the whole sub-continent, while all except one species of the order Machiloidea are confined to the discontinuous forest belt which lies below the escarpment of the inland plateau. The Machiloidea are not , however, strictly confined to the actual forests within their geographical region, some species invading regions of considerable aridity. Investigations on the ecology, water relations and orientation behaviour of a representative species of each order have been carried out. These have revealed that: (i) the physical conditions in the typical niche of the Machiloidea are extremely stable, whereas those in the habitat of the Lepismatoidea are subject to some considerable fluctuation. (ii) the Lepismatoidea are more resistant to desiccation than the Machiloidea; in both cases this resistance is due in part to physical barriers in the cuticle and partly to an active metabolic process. (iii) the Machiloidea rely on their eversible vesicles, situated on the abdominal coxosternites, for the uptake of water which cannot be drunk, such as a thin film of water or soil capillary water. (iv) the Lepismatoidea are able to absorb water from a subsaturated atmosphere. (v) the behavioural responses of both in respect of humidity, temperature, light and gravity, are such as to keep them in conditions within the range of their physiological limitations. From these results it is concluded that the Machiloidea can survive outside the shelter of forests, provided that water is readily available in some form in which it can be absorbed by the animals. The general implications of the results are such as to permit the erection of an hypothesis explaining the distribution of the Thysanura in South Africa in terms of t he availability of wate. The results also lead to speculations on the evolution of the Pterygota.
Keywords: Insects -- Adaptation; Insects -- Physiology; Thysanura; Apterygota